2000
DOI: 10.1063/1.126576
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahard carbon nanocomposite films

Abstract: An improved charge separation technique for metal-oxide-silicon (MOS) capacitors is presented which accounts for the deactivation of substrats dopants by hydrogen at elevated irradiation temperatures or small irradiation biases. Using high-frequency capacitance-voltage (C-V) measurements, radiation-induced inversion voltage shifts are separated into components due to oxide trapped charge, interface traps and deactivated dopants, where the latter is computed from a reduction in Si capacitance. In the limit of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…Siegal et al annealed nonhydrogenated a-C films produced by pulsed laser ablation and reported the presence, via high-resolution transmission electron microscopy, of regions 3 -5 nm in size that were 5-10 % more dense that the surrounding regions. 27 The as-deposited films have stresses of 5 -7 GPa and a film density of 3.0 g cm −3 but near-complete stress relief had occurred and the density had dropped to 2.8 g cm −3 with thermal annealing to 600°C. Over the same annealing temperature range the optical transparency of the film decreased, demonstrating that clustering of the sp 2 within the film is increasing.…”
Section: Clustering Disorder and Intracluster Effects In Amorpmentioning
confidence: 98%
“…Siegal et al annealed nonhydrogenated a-C films produced by pulsed laser ablation and reported the presence, via high-resolution transmission electron microscopy, of regions 3 -5 nm in size that were 5-10 % more dense that the surrounding regions. 27 The as-deposited films have stresses of 5 -7 GPa and a film density of 3.0 g cm −3 but near-complete stress relief had occurred and the density had dropped to 2.8 g cm −3 with thermal annealing to 600°C. Over the same annealing temperature range the optical transparency of the film decreased, demonstrating that clustering of the sp 2 within the film is increasing.…”
Section: Clustering Disorder and Intracluster Effects In Amorpmentioning
confidence: 98%
“…Overall, two main reasons Page 4 of 28 A c c e p t e d M a n u s c r i p t are expected to explain it. On the one hand, high residual stress ranging from 1~10 GPa lead to spall off from metallic substrates, at the same time, limit the film thickness [6][7][8]. This one could be effectively solved by the doping elements such as Ti, Cr, W and so on [9][10][11]; On the other hand, weak adhesive strength at the boundary between the film and substrate, which could be solved by the introduction of the addition Me, Me X C, Me X N interlayer [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…5 Nanocomposite or bilayer nanomaterials have interesting mechanical, electrical, optical and magnetic properties. [6][7][8][9][10][11] In the past, composite nanomaterials have been fabricated by electrochemical deposition, 12 sputter deposition 5 and FIB/FEB-CVD methods. We report here a method using FIB-and FEB-CVD processes to fabricate C-Pt core-shell like composite nanomechanical structures, consisting of a carbon nanowire core surrounded by a platinum outer layer shell.…”
Section: Introductionmentioning
confidence: 99%